Evaluating the Risk Acceptance Ladder (RAL) as a basis for targeting communication aimed at prompting attempts to improve health related behaviours: A pilot randomised controlled trial - Claire Stevens; Lion Shahab; Robert West (Frontiers Media S.A., 2015)
Abstract Objectives: To determine the utility of the Risk Acceptance Ladder (RAL) as a measure for gauging self-reported reasons for participation in a range of health behaviours, and as a basis for targeting behaviour change interventions. Design: Randomised controlled trial. Methods: A sample of 639 UK adults (18+ years) were recruited into an online study and asked about their participation in four health behaviours; smoking, alcohol consumption, physical activity, fruit and vegetable consumption. Those with a health behaviour to modify (N=130) were allocated a behaviour change target and completed the RAL. Eligible participants (N=97) were then randomised to one of two groups; an intervention group received brief motivating information based on their RAL response (on-target), the control received information mismatched to their RAL response (off-target). Following intervention delivery, behavioural response was measured by recording whether participants clicked on a link to find out more about changing their target behaviour. Results: Three-quarters (N= 97, 74.60%, 95% CI: 67.12 - 82.08) of participants felt the RAL provided a suitable response option that identified why they had not changed their target behaviour and 60% (N=78, 95% CI: 51.58 - 68.42) agreed that it was easy to select just one option. Logistic regression confirmed that those in the intervention group had greater odds of clicking the link than those in the control group (OR: 2.83, 95% CI: 1.01 - 7.91). Conclusions: The response to the RAL was generally positive and this pilot study provides tentative support for the use of the RAL to develop effective, targeted interventions.